2009
DOI: 10.1039/b815079f
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the coordination chemistry of bis(imino)acenaphthene (BIAN) ligands with s- and p-block elements

Abstract: Bis(imino)acenaphthenes (BIAN) have been known for many years. However, it is only since the 1990s that such compounds have been recognized as robust ligands for the support of catalytically active transition metal centers. More recently, the unique stereoelectronic properties of the BIAN ligand class are beginning to be appreciated and exploited for some fascinating new developments in synthetic, structural and catalytic s- and p-block chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
133
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 132 publications
(102 reference statements)
3
133
0
1
Order By: Relevance
“…Switching from [(dppbian)MgA C H T U N G T R E N N U N G (thf) 3 ] to [(dpp-bian)Ga-GaA C H T U N G T R E N N U N G (dpp-bian)] (1) the pathway for reaction with phenylacetylene changes from acid-base interaction (Scheme 1) to 1,3-dipolar cycloadditions. [9] From a structural point of view, digallene 1 illustrates the influence of the conformational rigidity and electronic lability of the ligand on the molecular structure and chemical properties of the complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Switching from [(dppbian)MgA C H T U N G T R E N N U N G (thf) 3 ] to [(dpp-bian)Ga-GaA C H T U N G T R E N N U N G (dpp-bian)] (1) the pathway for reaction with phenylacetylene changes from acid-base interaction (Scheme 1) to 1,3-dipolar cycloadditions. [9] From a structural point of view, digallene 1 illustrates the influence of the conformational rigidity and electronic lability of the ligand on the molecular structure and chemical properties of the complex.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Their transition-metal complexes were first reported by Elsevier and van Asselt in the early 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…41 Furthermore, the ease of preparation of BIAN complexes allows for the incorporation of a wide variety of Schiff bases. 46 Accordingly, we became interested in incorporating the BIAN motif into a known electrocatalytic system. Overall, cobaloximes exhibit three attributes that render them desirable for a study of a BIAN appendage, namely: (i) the capability for electrocatalytic activity, (ii) suitable axial binding sites for the substrates, and (iii) a ligand framework that is compatible with BIAN derivatization.…”
Section: Introductionmentioning
confidence: 99%
“…12 Interestingly, there are only a few instances in which BIAN ligands have been used for photoluminescent applications. [13][14][15][16] However, in a recently published study from our laboratory, it was reported that the BIAN ligand can be used as a support for AIE materials.…”
Section: Introductionmentioning
confidence: 99%